First‐Principles Optimization of Out‐of‐Plane Charge Transport in Dion–Jacobson CsPbI3 Perovskites with π‐Conjugated Aromatic Spacers. (2nd May 2021) - Fang, Zhi; Hou, Xinmei; Zheng, Yapeng; Yang, Zuobao; Chou, Kuo‐Chih; Shao, Gang; Shang, Minghui; Yang, Weiyou; Wu, Tom
Abstract: Quasi‐2D CsPbI3 perovskites have emerged as excellent candidates for advanced photovoltaic technologies due to their fundamentally enhanced stability than conventional 3D counterparts. However, the applications of quasi‐2D perovskites are plagued with their poor out‐of‐plane carrier mobility induced by the intercalated insulating organic layers. In this work, a new strategy is explored to significantly enhance the out‐of‐plane charge transport in quasi‐2D Dion–Jacobson (DJ) CsPbI3 perovskites via leveraging the intercalation of aromatic diamine cations ( p ‐phenylenediamine, PPDA) with unique π‐conjugated bond based on the first‐principles calculations. The strong interactions between PPDA 2+ cations and inorganic Pb‐I framework (i.e., I–I interaction, p ‐π coupling, and H‐bonds) provide three carrier pathways to facilitate the out‐of‐plane charge transport. Furthermore, the restricted in‐plane and out‐of‐plane structural distortion induced by the π‐conjugated bond could improve the electronic coupling and charge mobility along the out‐of‐plane direction with reduced bandgaps. As a proof of concept, the calculated average photovoltaic conversion efficiency of such engineered DJ CsPbI3 perovskite solar cells is ≈17%, which is very close to the certificated champion efficiency of 3D α‐CsPbI3, underscoring their potential for solar cell applications. Abstract : Application of intercalated π‐conjugated aromatic spacers is proposed as a novel strategy toward engineering quasi‐2D Dion–Jacobson perovskites, which can significantly enhance out‐of‐plane charge transport, with improved stability and reduced bandgap for achieving a photovoltaic conversion efficiency around 17%.